A metal-free and mild approach to 1, 3, 4-oxadiazol-2(3H)-ones via oxidative C–C bond cleavage using molecular oxygen. Issue 12 (7th March 2018) - Lim, Bumhee; Park, Seunggun; Park, Jae Hyun; Gam, Jongsik; Kim, Sanghee; Yang, Jung Woon; Lee, Jeeyeon
Abstract : A metal-free aerobic oxidative C–C bond cleavage reaction for the synthesis of 1, 3, 4-oxadiazol-2(3 H )-ones is described. Abstract : A mild metal-free approach to 1, 3, 4-oxadiazol-2(3 H )-ones via 1, 3, 4-oxadiazin-5(6 H )-ones is described. This novel transformation, promoted by the electron-withdrawing p -substituents on the phenyl group at the α-carbonyl position, features a tandem reaction consisting of oxidative hydroxylation and C–C bond cleavage using molecular oxygen. The method utilizes K2 CO3 in CH3 CN without any oxidants, transition metals, or additives, enabling the tunable synthesis of 1, 3, 4-oxadiazin-5(6 H )-ones, 1, 3, 4-oxadiazol-2(3 H )-ones, and α-ketoamides under mild aerobic conditions.